Development of novel biopolymers for bioactive coating of implantable medical device and drug delivery - Fojas, Jhalique Jane R.
Bioactivity and biocompatibility are the prerequisite properties of polymers intended to be used in medical application such as coating for scaffolds and components for drug delivery formulations. In this study, three new materials were developed: a novel polymer matrix, carrageenan-chitosan-hyaluronan (CA-CH-HY) as a bioactive coating for implantable metallic stents and devices, and synthesized polymers, N-Laurol chitosan and poly-lactic-co-glycodic acid (PLGA) based polyethylene glycolylated (PEGylated) formulations as effective components for controlled drug release delivery systems. Physical and chemical characterization of the polymers were done using attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), gel permeation chromatography (GPC), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and nuclear magnetic resonance (NMR). Surface morphology and size evaluation of the polymer-coated scaffolds were done using scanning electron microscopy (SEM) while the nanoengineered drug carriers were evaluated through transmitting electron microscopy (TEM). Biological analyses included cytotoxicity test and bioactivity assays such as bicinchoninic acid assay (BCA assay), enzyme linked immunosorbent assay (ELISA) and western blot. Further analysis was conducted for the nanoparticle drug delivery formulations using Zeta, release studies and real time quantitative polymerase chain reaction (qPCR).